Bending behavior of additively manufactured short fiber reinforced composite sandwich structures based on triply periodic minimal surface - Yaozhong Wu; Xuepeng Li; Shaoan Li; HuaWei Wang; Peng Wang; Weijia Li (Polymer Testing)
Triply periodic minimal surfaces (TPMSs) have gained increasing attention because of their excellent mechanical properties and scalability. The Gyroid TPMS core sandwich (G-TPMS sandwich) structure was designed, and its bending performance and failure behavior were studied through experimental, theoretical, and numerical approaches. The test samples were prepared by the fused deposition modeling (FDM) method using the carbon fiber reinforced nylon filament. Theoretical and numerical models were established and verified using experimental results. In addition, the influence of geometrical parameters on the bending performance and failure behavior of the G-TPMS sandwich structures was studied by parametric studies. The results show that the flexural modulus and peak load of the sandwich structures can be enhanced by increasing the relative density of the G-TPMS core and the face sheet thickness. The flexural modulus and the peak load of the G-TPMS sandwich structure with a face sheet thickness of 2.5 mm are 35.46 % and 36 % higher than that of the G-TPMS sandwich structure with a face sheet thickness of 1.5 mm, respectively. The flexural modulus and the peak load of the G-TPMS sandwich structure with a relative density of 0.35 are 37.5 % and 41.02 % higher than that of the G-TPMS sandwich structure with a relative density of 0.25. Meanwhile, the G-TPMS sandwich structures with a lower relative density of the core are prone to shear failure mode. The proposed G-TPMS sandwich has the potential to be applied in lightweight structures for aerospace, automotive, or marine engineering.